Price transmission and supply response: the case of Indian small cardamom: Indian small cardamom – Price analysis - Indhushree, A; Kuruvila, A (Journal of Spices and Aromatic Crops, 2021)
Market price volatility, the major challenge faced by the cardamom exporters greatly hinders the investment and destabilizes the earning of small holders. The present study attempted to analyse the price transmission between Indian and international markets and study the supply response of small cardamom to changes in price. The co-movement of prices of small cardamom exist between the Indian and international markets after trade liberalisation and the price transmission has been from the international market to the Indian market. The short-run disequilibrium has been found between the Indian and international prices of cardamom, which got corrected with varying speed of adjustment. The positive and significant elasticity of supply of small cardamom with respect to its own two year lagged price has been established. Crop specific price stabilization mechanism would help to overcome the wide fluctuations in prices of small cardamom.